Composite semipermeable membrane and method for producing the same

A composite semipermeable membrane with a crosslinked polyamide layer and controlled group ratios addresses the issues of water production and chemical durability, ensuring effective neutral molecule removal and resistance to acids, alkalis, and oxidants.

JP2025018122APending Publication Date: 2025-02-06TORAY INDUSTRIES INC

Patent Information

Application Number
JP2023121565
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-02-06

AI Technical Summary

Technical Problem

Conventional composite semipermeable membranes face issues with insufficient water production and selective separation of neutral molecules, and lack durability against chemicals commonly found in water treatment facilities.

Method used

The composite semipermeable membrane incorporates a crosslinked polyamide separation functional layer with controlled ratios of azo and nitro groups, optimized zeta potential, and specific chromaticity, manufactured through a process involving polycondensation, diazonium salt formation, and chemical modification to enhance durability and separation performance.

Benefits of technology

The membrane achieves high water production and effective neutral molecule removal while maintaining durability against chemicals, with minimal performance degradation under harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025018122000001
    Figure 2025018122000001
  • Figure 2025018122000002
    Figure 2025018122000002
Patent Text Reader

Abstract

To provide a composite semipermeable membrane which achieves both high water generation performance and neutral molecule removability, and has composite durability against chemicals including an acid, an alkali and an oxidant.SOLUTION: A composite semipermeable membrane includes a support membrane, and a separation function layer, wherein the separation function layer contains crosslinked polyamide having an azo group and a nitro group, and a ratio A of the azo group and a ratio B of the nitro group in the separation function layer satisfy 0.10≤A / B≤0.50.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to composite semipermeable membranes useful for the selective separation of liquid mixtures. [Background technology]

[0002] Regarding the separation of mixtures, there are various techniques for removing substances (e.g. salts) dissolved in a solvent (e.g. water). In recent years, the use of membrane separation methods as an energy- and resource-saving process has expanded.

[0003] Examples of membranes used in membrane separation methods include microfiltration membranes, ultrafiltration membranes, nanofiltration membranes, reverse osmosis membranes, etc. These membranes are used, for example, for producing drinking water or industrial ultrapure water from seawater, brackish water, water containing harmful substances, etc., for wastewater treatment, and for recovering valuable materials.

[0004] Many of the reverse osmosis membranes and nanofiltration membranes currently on the market are composite semipermeable membranes. Among them, a composite semipermeable membrane (Patent Document 1) obtained by coating a microporous support membrane with a separation functional layer made of a crosslinked aromatic polyamide obtained by a polycondensation reaction between a polyfunctional amine and a polyfunctional acid halide is widely used as a separation membrane with high water generation properties and high selective separation properties for salts and neutral molecules. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2010 / 096563 Summary of the Invention [Problem to be solved by the invention]

[0006] However, when using conventional composite semipermeable membranes to remove neutral molecules contained in raw water, their water production and selective separation properties were insufficient, posing problems in terms of membrane performance.

[0007] Furthermore, in various water treatment facilities such as water production plants, composite semipermeable membranes may come into contact with various chemicals such as acids, alkalis, and oxidizing agents, and are therefore required to have a composite durability against these chemicals.

[0008] Therefore, an object of the present invention is to provide a composite semipermeable membrane which has both high water generating ability and neutral molecule removing ability, and also has a composite durability against chemicals such as acids, alkalis, and oxidizing agents. [Means for solving the problem]

[0009] In order to solve the above problems, the present invention includes the following configurations. [1] A composite semipermeable membrane comprising a support membrane and a separation functional layer, the separation functional layer containing a crosslinked polyamide having an azo group and a nitro group, and wherein a ratio A of the azo group and a ratio B of the nitro group in the separation functional layer satisfy 0.10≦A / B≦0.50. [2] The composite semipermeable membrane according to [1] above, wherein the ratio A of azo groups, the ratio B of nitro groups, and the ratio C of amide groups in the separating functional layer satisfy 0.010≦(A+B) / C≦0.050. [3] The composite semipermeable membrane according to [1] or [2] above, wherein the zeta potential of the surface of the separation functional layer in a 10 mM sodium chloride aqueous solution at pH 7 is -70 mV or more and -35 mV or less. [4] The composite semipermeable membrane according to any one of the above [1] to [3], wherein the chromaticity b* of the surface of the separating functional layer is 5 or more and 20 or less. [5] A method for producing a composite semipermeable membrane comprising a support membrane and a separation functional layer provided on the support membrane, comprising: (a) forming a crosslinked polyamide on the support membrane by polycondensation of a polyfunctional amine with a polyfunctional acid halide; (b) contacting the crosslinked polyamide simultaneously with a compound (I) that reacts with a primary amino group to form a diazonium salt or a derivative thereof, and an oxidizing agent; A method for producing a composite semipermeable membrane comprising the steps of: [6] The method for producing a composite semipermeable membrane according to the above [5], wherein in the step (b), the mass ratio of the oxidizing agent to the compound (I) is 2 or more and 10 or less. [7] The method for producing a composite semipermeable membrane according to [5] or [6] above, wherein the step (b) comprises contacting an aqueous solution containing both the compound (I) and an oxidizing agent with the crosslinked polyamide, the temperature of the aqueous solution being 20°C or higher and 50°C or lower, and the contact time with the crosslinked polyamide being 10 seconds or higher and 10 minutes or shorter. [8] The method for producing a composite semipermeable membrane according to any one of [5] to [7] above, further comprising the step of contacting the crosslinked polyamide with sodium hydrogen sulfite or sulfite ions after the step (b). [9] The amount of multifunctional amine contained in the composite semipermeable membrane is 10 mg / m 2 More than 80mg / m 2 A method for producing a composite semipermeable membrane according to any one of the above [5] to [8], Effect of the Invention

[0010] According to the present invention, it is possible to provide a composite semipermeable membrane which has both high water generating ability and neutral molecule removing ability, and also has high durability against contact with multiple chemicals. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to these in any way.

[0012] (1) Composite semipermeable membrane The composite semipermeable membrane of the present invention comprises a support membrane and a separation functional layer. The separation functional layer is preferably present on one side of the support membrane.

[0013] (1-1) Separation functional layer (1-1-1) Composition In the composite semipermeable membrane of the present invention, it is the separation functional layer that has substantial solute separation performance. The separation functional layer contains a crosslinked polyamide, and preferably contains a crosslinked polyamide as a main component.

[0014] The phrase "X contains Y as a main component" means that Y accounts for 50% or more by mass of X, and also includes the case where X is composed of Y alone.

[0015] The term "crosslinked polyamide" refers to a polycondensate of a polyfunctional amine and a polyfunctional acid halide, in which at least one of the polyfunctional amine and the polyfunctional acid halide is trifunctional or higher. When at least one of the polyfunctional amine and the polyfunctional acid halide is trifunctional or higher, reactive functional groups are present on the polyamide main chain, and the polyamide main chain is crosslinked via the reactive functional groups.

[0016] The polyfunctional amine and polyfunctional acid halide constituting the crosslinked polyamide may contain at least one type of trifunctional or higher polyfunctional amine and / or polyfunctional acid halide, or may contain multiple types, and may further contain a difunctional amine and / or a difunctional acid halide.

[0017] The term "polyfunctional amine" refers to an amine having at least two primary amino groups and / or secondary amino groups in one molecule, at least one of which is a primary amino group. Examples of polyfunctional amines include polyfunctional aromatic amines such as phenylenediamine, xylylenediamine, 1,3,5-triaminobenzene, 1,2,4-triaminobenzene, 3,5-diaminobenzoic acid, 3-aminobenzylamine, and 4-aminobenzylamine, in which two amino groups are bonded to a benzene ring at the ortho, meta, or para positions, aliphatic amines such as ethylenediamine and propylenediamine, and alicyclic polyfunctional amines such as 1,2-diaminocyclohexane, 1,4-diaminocyclohexane, 4-aminopiperidine, and 4-aminoethylpiperazine.

[0018] Among them, the polyfunctional amine is preferably a polyfunctional aromatic amine having 2 to 4 primary amino groups and / or secondary amino groups in one molecule. Examples of such polyfunctional aromatic amines include m-phenylenediamine (hereinafter referred to as "m-PDA"), p-phenylenediamine, and 1,3,5-triaminobenzene. In order to achieve high selective separation properties, permeability, and heat resistance, it is preferable that 80 mass% or more of the polyfunctional amine-derived sites constituting the crosslinked polyamide are occupied by polyfunctional aromatic amines.

[0019] The term "polyfunctional acid halide" refers to an acid halide having at least two halogenated carbonyl groups in one molecule. Examples of trifunctional acid halides include trimesoyl chloride (hereinafter referred to as "TMC"), 1,3,5-cyclohexanetricarboxylic acid trichloride, and 1,2,4-cyclobutanetricarboxylic acid trichloride.

[0020] Examples of the bifunctional acid halides include aromatic bifunctional acid halides such as biphenyldicarboxylic acid dichloride, azobenzenedicarboxylic acid dichloride, terephthalic acid chloride, isophthalic acid chloride, and naphthalenedicarboxylic acid chloride; aliphatic bifunctional acid halides such as adipoyl chloride and sebacoyl chloride; and alicyclic bifunctional acid halides such as cyclopentanedicarboxylic acid dichloride, cyclohexanedicarboxylic acid dichloride, and tetrahydrofurandicarboxylic acid dichloride.

[0021] Considering the reactivity with polyfunctional amines, the polyfunctional acid halide is preferably a polyfunctional acid chloride (hereinafter referred to as "acid chloride"), more preferably a polyfunctional aromatic acid chloride having 2 to 4 carbonyl chloride groups in one molecule. The polyfunctional acid halide is further preferably TMC.

[0022] The separation functional layer is preferably a pleated thin film. This thin film preferably contains crosslinked polyamide as a main component. From the viewpoint of obtaining sufficient separation performance and water production amount, the thickness of the thin film is preferably 8 nm to 20 nm, more preferably 9 nm to 13 nm.

[0023] (1-1-2) Characteristics The separating functional layer in the composite semipermeable membrane of the present invention contains a crosslinked polyamide having an azo group and a nitro group, and the ratio A of the azo group and the ratio B of the nitro group in the separating functional layer satisfy 0.10≦A / B≦0.50.

[0024] "Ratio A of azo groups" means the ratio of the number of azo groups to the number of all functional groups having a nitrogen atom in the separation functional layer.

[0025] "Nitro group ratio B" means the ratio of nitrogen atoms derived from nitro groups to the total nitrogen atoms in the separating functional layer.

[0026] Both the "azo group ratio A" and the "nitro group ratio B" can be calculated by the method described later in "Measurement of the azo group ratio, nitro group ratio, and amide group ratio in the separation functional layer." Also, A / B corresponds to the ratio of azo groups to nitro groups contained in the separation functional layer.

[0027] The azo group and nitro group in the separation functional layer are generated, for example, by chemically converting the amino group at the end of the crosslinked polyamide. When 0.10≦A / B≦0.50 is satisfied, the pore structure of the separation functional layer can be optimized and hydrophilicity is improved, so that the water generating ability and the removal performance of salts and neutral molecules can be improved. In addition, the introduction of nitro groups suppresses decomposition due to contact with complex chemicals such as acid, alkali, and chlorine, and reduces the deterioration of separation performance. From the above viewpoint, A / B is preferably 0.15 or more, more preferably 0.20 or more. On the other hand, A / B is preferably 0.45 or less, more preferably 0.40 or less.

[0028] The ratio A of the azo group and the ratio B of the nitro group in the separating functional layer can be controlled by the concentrations of the compound (I) and the oxidizing agent, the reaction time, the reaction temperature, and the like, which will be described later.

[0029] The term "neutral molecule" refers to a non-ionic substance, and examples thereof include silica (hereinafter, "Si"), boron, and 2-propanol.

[0030] (1-2) Support membrane The support membrane in the composite semipermeable membrane of the present invention has at least a porous support layer. The support membrane may further have a substrate.

[0031] The porous support layer serves as a scaffold for forming a separation functional layer, and does not itself have substantial separation performance for ions, etc.

[0032] The size and distribution of the pores in the porous support layer are not particularly limited, but for example, a porous support layer having uniform, fine pores or gradually larger fine pores from the surface on which the separation functional layer is formed to the other surface, and in which the size of the fine pores on the surface on which the separation functional layer is formed is 0.1 nm or more and 100 nm or less, is preferred.

[0033] Examples of the material for the porous support layer include homopolymers or copolymers such as polysulfone, polyethersulfone, polyamide, polyester, cellulose-based polymer, vinyl polymer, polyphenylene sulfide, polyphenylene sulfide sulfone, polyphenylene sulfone, and polyphenylene oxide, and these can be used alone or in blends. Here, examples of the cellulose-based polymer include cellulose acetate and cellulose nitrate, and examples of the vinyl polymer include polyethylene, polypropylene, polyvinyl chloride, and polyacrylonitrile. Among these, examples of the material for the porous support layer include homopolymers or copolymers such as polysulfone, polyamide, polyester, cellulose acetate, cellulose nitrate, polyvinyl chloride, polyacrylonitrile, polyphenylene sulfide, and polyphenylene sulfide sulfone, and more preferably cellulose acetate, polysulfone, polyphenylene sulfide sulfone, or polyphenylene sulfone. Furthermore, among these materials, polysulfone is generally preferably used because it has high chemical, mechanical, and thermal stability and is easy to mold.

[0034] The morphology of the porous support layer can be observed by a scanning electron microscope, a transmission electron microscope, an atomic force microscope, or the like. For example, when observing by a scanning electron microscope, the porous support layer is peeled off from the substrate, and then cut by freeze fracturing to obtain a sample for cross-sectional observation. This sample is thinly coated with platinum, platinum-palladium, or ruthenium tetrachloride, preferably ruthenium tetrachloride, and observed by a high-resolution field emission scanning electron microscope (UHR-FE-SEM) at an accelerating voltage of 3 to 15 kV. For example, an S-900 type electron microscope manufactured by Hitachi, Ltd. can be used as the high-resolution field emission scanning electron microscope.

[0035] The thickness of the porous support layer is preferably 20 μm or more and 100 μm or less from the viewpoints of obtaining a good pressure resistance, obtaining a uniform porous support layer without defects, and reducing the amount of polyfunctional amine remaining as a monomer component after polyamide synthesis. The thickness range for achieving both the membrane performance and the reduction in the amount of polyfunctional amine remaining in the porous support layer is more preferably 20 μm or more and 45 μm or less, and even more preferably 20 μm or more and 31 μm or less.

[0036] When the support film has a substrate, the thickness of the support film is preferably 30 μm or more and 300 μm or less, and more preferably 100 μm or more and 220 μm or less.

[0037] In the composite semipermeable membrane of the present invention, the ratio A of azo groups, the ratio B of nitro groups and the ratio C of amide groups in the separating functional layer preferably satisfy 0.010≦(A+B) / C≦0.050.

[0038] The "ratio C of amide groups" refers to the ratio of the number of amide groups to the number of all functional groups having a nitrogen atom in the separation functional layer. It can be calculated by the method described later in "Measurement of the ratio of azo groups, the ratio of nitro groups, and the ratio of amide groups in the separation functional layer."

[0039] (A+B) / C means the ratio of the sum of the ratio of azo groups and the ratio of nitro groups to the ratio of amide groups in the separation functional layer. (A+B) / C of 0.010 or more indicates that the terminal amino groups of the crosslinked polyamide have been sufficiently converted to azo groups or nitro groups.

[0040] From the viewpoint of obtaining sufficient water generating properties and neutral molecule removing ability by introducing azo and nitro groups, and high durability against contact with multiple chemicals, (A+B) / C is more preferably 0.015 or more, and even more preferably 0.020 or more. On the other hand, the ratio C of amide groups is an index representing the degree of crosslinking in the separation functional layer, and from the viewpoint of obtaining a membrane with sufficient strength by setting the ratio of amide groups at a certain level or more, (A+B) / C is more preferably 0.045 or less, and even more preferably 0.040 or less.

[0041] (A+B) / C can be controlled by the concentrations of compound (I) and the oxidizing agent, the reaction time, the reaction temperature, and the like, which will be described later.

[0042] In the composite semipermeable membrane of the present invention, the zeta potential of the surface of the separating functional layer in a pH 7, 10 mM sodium chloride (hereinafter, "NaCl") aqueous solution is preferably -70 mV or more and -35 mV or less.

[0043] When the amino group at the end of the crosslinked polyamide is converted to an azo group and then further converted to an azosulfonate group, the amount of negative charge on the surface of the separation functional layer increases. By setting the zeta potential of the surface of the separation functional layer of the composite semipermeable membrane under neutral conditions to the above range, the removal performance of salts and neutral molecules is improved. The zeta potential of the surface of the separation functional layer in a 10 mM NaCl aqueous solution at pH 7 is more preferably -65 mV or more and -38 mV or less, and even more preferably -60 mV or more and -40 mV or less. The zeta potential of the surface of the separation functional layer in a 10 mM NaCl aqueous solution at pH 3 is more preferably -35 mV or more and -5 mV or less. The fact that the zeta potential of the surface of the separation functional layer is in the above range even under acidic conditions means that the conversion of the terminal amino group of the crosslinked polyamide is sufficiently performed, which contributes to improving the membrane performance under neutral conditions.

[0044] The zeta potential of the surface of the separating functional layer can be controlled by the concentration of the water-soluble compound (II), reaction time, reaction temperature, and the like, which will be described later.

[0045] The chromaticity b* of the surface of the separating functional layer in the composite semipermeable membrane of the present invention is preferably 5 or more and 20 or less.

[0046] The chromaticity b* of the surface of the separation functional layer increases due to the azotization of the terminal amino group of the crosslinked polyamide. However, the chromaticity b* of the surface of the separation functional layer and the performance of the composite semipermeable membrane are not simply proportional to each other. If the azo groups are present to such an extent that the chromaticity b* of the surface of the separation functional layer is 5 or more, the performance of the composite semipermeable membrane is sufficiently improved, so that the chromaticity b* of the surface of the separation functional layer is more preferably 5 or more, and even more preferably 7 or more. On the other hand, when the azo groups are introduced into the separation functional layer, low molecular weight components such as unreacted polyfunctional amines and oligomers remaining in the separation functional layer are also azotized, and when the amount of low molecular weight components is large, the chromaticity b* of the surface of the separation membrane functional layer increases. From the viewpoint of suppressing the degradation of the performance of the separation membrane due to the decomposition and elution of these azotized low molecular weight components due to contact with multiple chemicals, the chromaticity b* of the surface of the separation functional layer is more preferably 20 or less, more preferably 15 or less, and particularly preferably 13 or less.

[0047] The chromaticity b* of the composite semipermeable membrane is based on the L*a*b* color system (CIE1976L*a*b* color space), and is obtained by measuring the reflected color from the separation functional layer surface of the composite semipermeable membrane using a colorimeter conforming to JIS Z 8722:2009 (method of measuring color). At that time, it is preferable to perform the measurement using SCI (including specular reflection) since a constant value can be obtained regardless of the dry or wet state of the composite semipermeable membrane.

[0048] The chromaticity b* of the surface of the separating functional layer can be controlled by the hot water washing temperature, washing time, etc. after the formation of the support membrane.

[0049] (2) Manufacturing method (2-1) Formation process of porous support layer The step of forming the porous support layer includes a step of applying a polymer solution to a substrate or a base material and a step of immersing the substrate with the applied solution in a coagulation bath to coagulate the polymer. When the porous support layer is formed on a base material, the base material is peeled off from the porous support layer. The support film may be composed of a substrate and a porous support layer.

[0050] The step of forming the porous support layer may further include a step of preparing a polymer solution by dissolving the polymer in a good solvent for the polymer. As a method for forming the porous support layer, a known technique can be suitably used.

[0051] The temperature of the polymer solution during application is preferably 10°C or higher and 60°C or lower. If the temperature of the polymer solution is within this range, the polymer does not precipitate, and the polymer solution is solidified after fully impregnating the spaces between the fibers of the substrate. As a result, the porous support layer is firmly bonded to the substrate due to the anchor effect, and a good support film can be obtained. The preferred temperature range of the polymer solution can be appropriately adjusted depending on the type of polymer used, the desired solution viscosity, etc.

[0052] After the polymer solution is applied onto the substrate, the time until the substrate is immersed in the coagulation bath is preferably 0.1 seconds or more and 5 seconds or less. If the time until the substrate is immersed in the coagulation bath is within this range, the organic solvent solution containing the polymer is sufficiently impregnated into the spaces between the fibers of the substrate and then solidified. The preferred range of the time until the substrate is immersed in the coagulation bath can be appropriately adjusted depending on the type of polymer solution used, the desired solution viscosity, and the like.

[0053] The coagulation bath is generally water, but is not particularly limited as long as it does not dissolve the polymer that is a component of the porous support layer. The form of the obtained porous support layer changes depending on the composition of the coagulation bath, and the obtained composite semipermeable membrane also changes accordingly. The temperature of the coagulation bath is preferably -20°C or higher and 100°C or lower, and more preferably 10°C or higher and 50°C or lower. If the temperature of the coagulation bath is within this range, the vibration of the coagulation bath surface due to thermal motion does not become intense, and the smoothness of the surface of the porous support layer after formation is maintained. Furthermore, if the temperature is within this range, the coagulation speed is appropriate and the membrane formability is good.

[0054] Next, the support membrane thus obtained is washed with hot water to remove the solvent remaining in the membrane. The temperature of the hot water at this time is preferably 40°C or higher and 100°C or lower, more preferably 60°C or higher and 95°C or lower. Within this range, the shrinkage of the support membrane does not increase and the amount of water produced is good. Furthermore, within this range of temperature, a sufficient washing effect can be obtained.

[0055] The above specific conditions are suitable when polysulfone is used as the material for the porous support layer.

[0056] (2-2) Formation process of separation functional layer Next, the process of forming the separation functional layer constituting the composite semipermeable membrane will be described. In the process of forming the separation functional layer of the present invention, an aqueous solution containing a polyfunctional amine and a solution in which a polyfunctional acid halide is dissolved in an organic solvent are used to carry out interfacial polycondensation on the surface of the support membrane including the substrate and the porous support layer to form a crosslinked polyamide. From the viewpoint of removal performance, the crosslinked polyamide is preferably a crosslinked aromatic polyamide.

[0057] The term "crosslinked aromatic polyamide" refers to a polycondensation product of a polyfunctional aromatic amine and a polyfunctional aromatic acid halide, in which at least one of the polyfunctional aromatic amine and the polyfunctional aromatic acid halide is trifunctional. The polyfunctional aromatic amine and the polyfunctional aromatic acid halide constituting the crosslinked aromatic polyamide may contain at least one type of trifunctional or higher polyfunctional aromatic amine and / or polyfunctional aromatic acid halide, or may contain multiple types, and may further contain a bifunctional aromatic amine and / or a bifunctional aromatic acid halide.

[0058] Hereinafter, the process will be described taking as an example a case where a polyfunctional aromatic amine is used as the polyfunctional amine and a polyfunctional aromatic acid chloride is used as the polyfunctional acid halide.

[0059] The organic solvent for dissolving the polyfunctional acid halide may be any solvent that is immiscible with water, does not destroy the support film, and does not inhibit the reaction for producing the crosslinked aromatic polyamide. For example, hydrocarbons such as octane, nonane, decane, undecane, dodecane, tridecane, tetradecane, heptadecane, hexadecane, cyclooctane, ethylcyclohexane, 1-octene, and 1-decene, or halogenated hydrocarbons such as trichlorotrifluoroethane may be used alone or in combination of two or more solvents.

[0060] In order to carry out the interfacial polycondensation on the porous support layer, the surface of the porous support layer is first coated with an aqueous solution of a polyfunctional aromatic amine.

[0061] The method of coating the surface of the porous support layer with the aqueous polyfunctional aromatic amine solution may be any method that can uniformly and continuously coat the surface of the porous support layer with the aqueous solution, and may be carried out by a known coating method, such as a method of coating the surface of the porous support layer with the aqueous solution or a method of immersing the porous support layer in the aqueous solution. The contact time between the porous support layer and the aqueous polyfunctional aromatic amine solution is preferably within a range of 5 seconds to 10 minutes, and more preferably within a range of 10 seconds to 3 minutes. Next, it is preferable to remove the excess aqueous solution by a draining process. As a method of draining, for example, a method of holding the membrane surface vertically and allowing it to flow naturally may be used. After draining, the membrane surface may be dried to remove all or part of the water in the aqueous solution.

[0062] Then, the above-mentioned polyfunctional aromatic acid chloride solution is applied to the porous support layer coated with the polyfunctional aromatic amine aqueous solution, and a crosslinked aromatic polyamide is formed by interfacial polycondensation. The time for carrying out the interfacial polycondensation is preferably 0.1 seconds to 3 minutes, more preferably 0.1 seconds to 1 minute.

[0063] The concentration of the polyfunctional aromatic acid chloride in the polyfunctional aromatic acid chloride-containing solution is not particularly limited, but from the viewpoint of forming a defect-free separation functional layer and from the viewpoint of production costs, it is preferably 0.01 mass % or more and 1.0 mass % or less.

[0064] Next, the organic solvent remaining after the reaction is preferably removed by a draining process. For example, the organic solvent can be removed by holding the membrane vertically and allowing the excess organic solvent to flow down naturally. In this case, the time for holding vertically is preferably 1 minute or more and 5 minutes or less, and more preferably 1 minute or more and 3 minutes or less. Holding for 1 minute or more makes it easier to obtain a crosslinked aromatic polyamide having the desired function, and holding for 3 minutes or less can suppress the occurrence of defects due to overdrying of the organic solvent, thereby suppressing performance degradation.

[0065] The composite semipermeable membrane obtained by the above method is preferably subjected to a step of hot water treatment or the like in order to reduce the amount of polyfunctional amine contained in the composite semipermeable membrane. After hot water washing, the amount of polyfunctional amine contained in the support membrane and the separating functional layer is 10 mg / m 2 More than 80mg / m 2 It is preferable that the concentration is 20 mg or more and 70 mg or less, and more preferable that the concentration is 30 mg / m 2 More than 60mg / m 2 It is even more preferable that:

[0066] The amount of polyfunctional amine remaining in the support membrane and separation functional layer is 10 mg / m 2 More than 80mg / m 2 A specific example of the method for achieving the above is washing the laminate of the support membrane and the separation functional layer with hot water for 1 second to 10 minutes, preferably 1 minute to 8 minutes, at a temperature of 50° C. to 150° C., preferably 70° C. to 130° C. Washing may be performed by immersion in hot water, exposure to running hot water, or the like.

[0067] The amount of multifunctional amine in the composite semipermeable membrane is 10 mg / m 2When the amount of polyfunctional amine in the composite semipermeable membrane is 80 mg / m or more, a preferable amount of azo groups is generated by the subsequent treatment. In particular, the chromaticity b* of the surface of the separation functional layer is 5 or more, and a composite semipermeable membrane having high removal performance is obtained. In addition, when the amount of polyfunctional amine in the composite semipermeable membrane is 80 mg / m or more, 2 By keeping it below this value, the generation of unnecessary azo groups is suppressed, so that the chromaticity b* of the surface of the separation functional layer becomes 20 or less, and durability against contact with multiple chemicals can be achieved.

[0068] The method for producing a composite semipermeable membrane of the present invention includes a step of simultaneously contacting a crosslinked polyamide with a compound (I) that reacts with a primary amino group to generate a diazonium salt or a derivative thereof and an oxidizing agent. The means for contacting the composite semipermeable membrane with the reagent is not particularly limited, but from the viewpoint of sufficiently carrying out the reaction, a method of immersing the composite semipermeable membrane in an aqueous solution containing the compound (I) and the oxidizing agent is preferred, and in this case, it is also preferred to increase the reaction efficiency by stirring.

[0069] Examples of the compound (I) that reacts with a primary amino group to generate a diazonium salt or a derivative thereof include nitrous acid or a salt thereof, a nitrosyl compound, etc. Since aqueous solutions of nitrous acid and nitrosyl compounds are easily decomposed, a method in which nitrous acid is successively generated by, for example, reacting a nitrite with an acidic solution is preferred.

[0070] In general, nitrite reacts with hydrogen ions to generate nitrous acid. At this time, nitrous acid is efficiently generated when the pH of the aqueous solution is 7 or less, preferably 5 or less, and more preferably 4 or less. Among them, it is particularly preferable to generate an aqueous nitrous acid solution by reacting hydrochloric acid or sulfuric acid with sodium nitrite in an aqueous solution, from the viewpoint of ease of handling.

[0071] As the oxidizing agent, a general oxidizing agent such as a water-soluble peroxide can be used. Among them, from the viewpoints of reactivity with the aromatic polyamide and ease of handling, the oxidizing agent is preferably a persulfuric acid compound, and more preferably a peroxymonosulfuric acid compound.

[0072] Since the oxidizing agent has a lower reactivity with amino groups than compound (I), the mass ratio of the oxidizing agent to compound (I) when they are simultaneously contacted with the crosslinked polyamide is preferably 2 or more. On the other hand, since the reaction between compound (I) and amino groups must also proceed in parallel, the mass ratio of the oxidizing agent to compound (I) is preferably 10 or less.

[0073] In addition, when compound (I) and the oxidizing agent are prepared as solutions of the same volume, and when compound (I) and the oxidizing agent are dissolved in the same solution, the concentration of the oxidizing agent is preferably 2 to 10 times the concentration of compound (I).

[0074] The concentration of compound (I) is preferably 0.1% by mass or more and 0.8% by mass or less. If the concentration of compound (I) is 0.1% by mass or more, the diazonium salt or its derivative is sufficiently generated. If the concentration of compound (I) is 0.8% by mass or less, the generation of nitrous acid gas and the like is suppressed, and the industrial handling of the solution becomes easy.

[0075] For example, when sodium nitrite is used as compound (I) and a peroxymonosulfuric acid compound is used as an oxidizing agent and the concentration of sodium nitrite is 0.1% by mass or more and 0.8% by mass or less, the concentration of the peroxymonosulfuric acid compound is preferably 0.2% by mass or more and 8% by mass or less, and more preferably 0.8% by mass or more and 5% by mass or less.

[0076] The temperature of the aqueous solution containing compound (I) and the oxidizing agent is preferably 20° C. or higher and 50° C. or lower. Within this temperature range, the reaction time is appropriate, decomposition of nitrous acid can be suppressed, and handling is easy.

[0077] The contact time of the aqueous solution containing compound (I) and an oxidizing agent with the composite semipermeable membrane may be the time required for the primary amino groups of compound (I) to react and produce a diazonium salt and / or its derivatives. At high concentrations, the treatment can be completed in a short time, but at low concentrations, a long treatment time is required. In addition, with respect to the oxidizing agent, it is required to convert the amino groups within a range that balances the durability and initial performance of the composite semipermeable membrane. Therefore, in the case of a solution of the above concentration, the contact time with the composite semipermeable membrane is preferably 10 seconds or more and 10 minutes or less, and more preferably 30 seconds or more and 3 minutes or less. Next, the composite semipermeable membrane in which the diazonium salt or its derivative is produced is contacted with a water-soluble compound (II) that reacts with the diazonium salt or its derivative. Examples of the water-soluble compound (II) that reacts with the diazonium salt or its derivative include chloride ions, bromide ions, cyanide ions, iodide ions, fluoroboric acid, hypophosphorous acid, sodium hydrogen sulfite, sulfite ions, hydrogen sulfide, and thiocyanic acid. Among these, when reacted with sodium hydrogen sulfite or sulfite ions, a substitution reaction occurs instantly, and a sulfo group is formed at the end. These compounds may be used alone, or may be used in a mixture of multiple compounds, or may be contacted multiple times with different compounds. Examples of preferred compounds to be contacted include sodium hydrogen sulfite and sulfite ions. It is preferable to contact the composite semipermeable membrane with the water-soluble compound (II) as a solution, particularly an aqueous solution dissolved in water.

[0078] The concentration and time for contacting the composite semipermeable membrane with the water-soluble compound (II) can be appropriately adjusted to obtain the desired effect.

[0079] The temperature at which the composite semipermeable membrane is contacted with the water-soluble compound (II) is preferably 10° C. or higher and 90° C. or lower. Within this temperature range, the reaction proceeds easily, while a decrease in the amount of permeated water due to shrinkage of the polymer can be suppressed.

[0080] (3) Use of composite semipermeable membranes The composite semipermeable membrane of the present invention is preferably used as a spiral-type composite semipermeable membrane element by being wound around a cylindrical water collection pipe having a large number of holes, together with a raw water flow passage material such as a plastic net, a permeate water flow passage material such as tricot, and, if necessary, a film for increasing pressure resistance. Furthermore, this element can be connected in series or in parallel and housed in a pressure vessel to form a composite semipermeable membrane module. Furthermore, the above-mentioned composite semipermeable membrane, composite semipermeable membrane element, and module can be combined with a pump that supplies raw water to them, a device that pretreats the raw water, etc. to form a fluid separation device. By using this separation device, raw water can be separated into permeated water, such as drinking water, and concentrated water that did not permeate the membrane, thereby obtaining water suitable for the purpose.

[0081] The higher the operating pressure of the fluid separation device, the better the removal performance of salts and the like. However, taking into consideration the increased energy required for operation and the durability of the composite semipermeable membrane, the operating pressure when the treated water is passed through the composite semipermeable membrane is preferably 0.1 MPa or more and 10 MPa or less. As the supply water temperature increases, the removal performance of salts and the like decreases, while as the supply water temperature decreases, the membrane permeation flux also decreases, so the supply water temperature is preferably 5°C or more and 45°C or less. In addition, in the case of supply water with a high salt concentration such as seawater, if the supply water pH becomes high, there is a risk of scale formation of magnesium and the like. Furthermore, there is a concern that membrane deterioration may occur due to high pH operation, so operation in the neutral region is preferable.

[0082] Examples of raw water to be treated by the composite semipermeable membrane of the present invention include liquid mixtures such as seawater, brackish water, and wastewater that contain a total dissolved solids content (hereinafter referred to as "TDS") of 500 mg / L to 100 g / L and nonionic substances of 0.1 mg / L to 1000 mg / L. Generally, TDS is expressed as "mass / volume" or "mass ratio." According to the definition, it can be calculated from the weight of the residue obtained by evaporating a solution filtered through a 0.45 μm filter at a temperature of 39.5° C. to 40.5° C., but it is more convenient to convert it from the practical salinity (S).

[0083] From the perspective of practicality, the initial water production rate of the composite semipermeable membrane is preferably 1.2 m 3 / m 2 / day or more, and more preferably 1.4 or more. When used as a reverse osmosis membrane, the initial NaCl removal rate and Si removal rate of the composite semipermeable membrane are preferably 99.3% or more, and more preferably 99.6% or more.

Examples

[0084] The present invention will be specifically described below with reference to examples, but the present invention is not limited thereto.

[0085] 1. Measurement of properties <Measurement of NaCl removal rate and Si removal rate> Evaluation water adjusted to a temperature of 25°C, pH 7, NaCl concentration of 2000 ppm, and Si concentration of 20 ppm was supplied to the composite semipermeable membrane at an operating pressure of 1.55 MPa for membrane filtration treatment. The electrical conductivity of the feed water and the permeate water was measured with a conductivity and pH meter (WM-50EG manufactured by East Asia TDK Corporation) to obtain the practical salinity of each, that is, the NaCl concentration. Based on the obtained NaCl concentration and the following formula (1), the NaCl removal rate was calculated. Note that "ppm" means the concentration based on mass. NaCl removal rate (%) = 100 × {1 - (NaCl concentration in permeate water / NaCl concentration in feed water)} ··· Formula (1) In addition, the Si concentrations of the feed water and the permeate water were measured with an ICP emission spectrometer (5110VDV manufactured by Agilent), and the Si removal rate was calculated from the following formula (2). Si removal rate (%) = 100 × {1 - (Si concentration in permeate water / Si concentration in feed water)} ··· Formula (2).

[0086] <Measurement of membrane permeation flux> In the test in the previous section, the membrane permeation water volume of the feed water (NaCl aqueous solution) was measured, and the value converted to the water permeation volume (cubic meters) per day per square meter of the membrane surface was defined as the membrane permeation flux (m 3 / m 2 / day).

[0087] <Combined Deterioration Test> (a) The composite semipermeable membrane was immersed in an aqueous sodium hydroxide solution at 30° C. and adjusted to pH 12.4 for 24 hours. (b) The composite semipermeable membrane was immersed in an aqueous sulfuric acid solution adjusted to pH 2 at 30° C. for 1 hour. (c) The composite semipermeable membrane was immersed for 96 hours in an aqueous solution at 25°C, which had been adjusted to a free chlorine concentration of 5 ppm and a pH of 7 using sodium hypochlorite and potassium dihydrogen phosphate, and then immersed for 10 minutes in a 0.1% by mass aqueous solution of sodium hydrogen sulfite at 25°C. The above steps (a)→(b) were repeated three times, followed by step (c) once, and then three more steps (a)→(b) in the order described above as a composite degradation test.

[0088] <Measurement of the amount of polyfunctional amine in the film> The composite semipermeable membrane (20 cm2) was wiped with Kimtowel to remove moisture from the surface of the separation functional layer before contacting with the compound (I) and / or the oxidizing agent. 2 The composite semipermeable membrane was immersed in 20 g of ethanol in a polypropylene container. After standing at 25°C for 19 hours, the absorbance at 288 nm of the ethanol in which the composite semipermeable membrane was immersed was measured using a spectrophotometer (Shimadzu UV-2450). A calibration curve of mPDA concentration and absorbance was prepared using an ethanol solution in which a predetermined concentration of m-PDA, a multifunctional amine constituting the separation functional layer, was dissolved. From the obtained absorbance, the absorbance of 1 m of the composite semipermeable membrane was calculated. 2 Amount of polyfunctional amine per unit (mg / m 2 The measurement was performed after correcting the absorbance at 288 nm of ethanol without immersing the composite semipermeable membrane to be 0.

[0089] <Measurement of the ratio of azo groups, nitro groups, and amide groups in the separation functional layer> Composite semipermeable membrane 5m 2The substrate was physically peeled off from the substrate, and the porous support layer and separation functional layer were collected. After drying by leaving it to stand at 25°C for 24 hours, it was added little by little to a beaker containing dichloromethane and stirred to dissolve the polymer that constitutes the porous support layer, and the insoluble matter in the beaker was collected with filter paper. This insoluble matter was placed in a beaker containing dichloromethane and stirred, and the insoluble matter in the beaker was collected. This operation was repeated until the elution of the polymer that forms the porous support layer could no longer be detected in the dichloromethane solution. The separation functional layer collected as insoluble matter was dried in a vacuum dryer to remove the remaining dichloromethane. The obtained separation functional layer was made into a powdered sample by freeze-pulverization, sealed in a sample tube used for solid-state NMR measurement, and analyzed by DD / MAS method. 13 C solid-state NMR measurements were carried out. 13 C solid-state NMR measurements were performed using an AVANCE 400 (manufactured by Bruker Biospin) under the following measurement conditions. Reference material: Silicone rubber (internal standard: 1.56 ppm) Sample rotation speed: 14kHz Pulse repetition time: 120s (DD / MAS method) From the obtained spectrum, the peaks derived from the carbon atoms bonded to nitrogen atoms were divided into carbon atoms bonded to azo groups, amide groups, and amino or nitro groups, and the peak area a of the carbon atoms bonded to azo groups, the peak area c of the carbon atoms bonded to amide groups, and the peak area d of the carbon atoms bonded to amino or nitro groups were calculated from the divided peaks. The ratio A of the azo groups in the separation functional layer was calculated using the following formula (3), and the ratio C of the amide groups was calculated using the following formula (4). Azo group ratio A = (a / 2) / (a / 2 + c + d) Equation (3) Ratio of amide groups C = c / (a / 2 + c + d) Equation (4) Next, the ratio B of the nitro group contained in the separation functional layer was calculated from the measurement results by XPS. 13 A powdered sample of the separation functional layer was obtained by carrying out the same treatment as the C solid-state NMR sample. The obtained powdered sample was molded into a pellet. The molded sample was subjected to XPS measurement. The measurement conditions are as follows: Measurement equipment: Quantera SXM (PHI) Excitation X-ray: monochromatic Al Kα1,2 line (1486.6 eV) X-ray diameter: 0.2 mm The N1s peak obtained by XPS is due to the inner shell electrons of nitrogen atoms. Since the N1s peak is composed of components derived from nitrogen atoms contained in amino groups, amide groups, and azo groups, and components derived from NOx (x≧2) contained in nitro groups, the N1s peak was divided into two components. The components derived from nitrogen atoms contained in amino groups, amide groups, and azo groups appear at around 400 eV, and the components derived from NOx (x≧2) appear at around 406 eV. The peak area of ​​the components derived from nitrogen atoms contained in amino groups, amide groups, and azo groups is e, and the peak area of ​​the components derived from NOx (x≧2) is b, and the ratio B of nitro groups in the separation functional layer was calculated using the following formula (5). Ratio of nitro groups B = b / (e + b) Equation (5) 13 From A and C obtained by C solid-state NMR measurement and B obtained by XPS measurement, A / B and (A+B) / C in the separation functional layer were calculated. A / B was rounded to the third decimal place, and (A+B) / C was rounded to the fourth decimal place.

[0090] <Measurement of chromaticity b* of the surface of the separation functional layer> The composite semipermeable membrane was immersed in water for 30 minutes or more, and in the state where the surface of the separation functional layer was wet, b* was measured from the surface of the separation functional layer in SCI mode using a colorimeter (Konica Minolta CM-25d) on a black laboratory bench. Ten randomly different points on the same composite semipermeable membrane were measured, and the average value was calculated.

[0091] <Zeta potential measurement> The composite semipermeable membrane was washed with ultrapure water, and placed in a flat sample cell so that the separation functional layer surface of the composite semipermeable membrane was in contact with the monitor particle solution, and measurements were made using a zeta potential, particle size, and molecular weight measurement system (ELSZneo, manufactured by Otsuka Electronics Co., Ltd.). The monitor particle solution used was a measurement solution in which polystyrene latex monitor particles were dispersed in a 10 mM NaCl aqueous solution adjusted to pH 7 and pH 3, respectively. Using the above measurement solution, the surface zeta potential α (pH 7, 10 mM NaCl aqueous solution) and surface zeta potential β (pH 3, 10 mM NaCl aqueous solution) of the separation functional layer were measured.

[0092] 2. Preparation of Composite Semipermeable Membrane [Reference example 1] A 15.0% by mass solution of polysulfone in DMF was cast onto a polyester nonwoven fabric made of long fibers (air permeability 2.0 cc / cm2 / s) at 25°C, and then immediately immersed in pure water and left for 5 minutes to produce a support membrane with a porous support layer thickness of 40 μm.

[0093] [Example 1] The support membrane obtained in Reference Example 1 was immersed in a 3.5% by mass m-PDA aqueous solution, after which excess aqueous solution was removed, and further a n-decane solution in which TMC was dissolved to a concentration of 0.15% by mass was applied so that the surface of the porous support layer was completely wet. Next, in order to remove excess solution from the membrane, the membrane was vertically drained, and then dried by blowing air at 25°C using a blower, and then immersed in hot water at 85°C for 2 minutes to wash. The amount of polyfunctional amine in the obtained composite semipermeable membrane was 32 mg / m 2 The obtained composite semipermeable membrane was immersed in an aqueous solution of 0.4 mass% sodium nitrite and 1 mass% potassium peroxymonosulfate at 35°C and pH 2 for 30 seconds, and then immersed in an aqueous solution of 0.1 mass% sodium sulfite for 2 minutes to obtain the composite semipermeable membrane of Example 1.

[0094] [Example 2] A composite semipermeable membrane of Example 2 was obtained in the same manner as in Example 1, except that after immersion for 30 seconds in an aqueous solution of 0.4 mass% sodium nitrite and 1 mass% potassium peroxymonosulfate at 35°C and pH 2, the membrane was not immersed in 0.1 mass% sodium sulfite.

[0095] [Example 3] A composite semipermeable membrane of Example 3 was obtained in the same manner as in Example 1, except that the concentration of potassium peroxymonosulfate was 0.4 mass %.

[0096] [Example 4] A composite semipermeable membrane of Example 4 was obtained in the same manner as in Example 1, except that the membrane was immersed in an aqueous solution containing 0.4% by mass of sodium nitrite and 1% by mass of potassium peroxymonosulfate at 35° C. and pH 2 for 10 seconds.

[0097] [Example 5] A composite semipermeable membrane of Example 5 was obtained in the same manner as in Example 1, except that it was immersed in hot water at 85° C. for 30 seconds. The amount of polyfunctional amine in the composite semipermeable membrane before immersion in the aqueous solution in which sodium nitrite and potassium peroxymonosulfate were dissolved was 90 mg / m 2 It was.

[0098] [Comparative Example 1] A composite semipermeable membrane of Comparative Example 1 was obtained in the same manner as in Example 1, except that the membrane was not immersed in an aqueous solution containing 0.4 mass % sodium nitrite and 1 mass % potassium peroxymonosulfate at 35° C. and pH 2.

[0099] [Comparative Example 2] The membrane obtained in Comparative Example 1 was immersed in a 0.4 mass % sodium nitrite aqueous solution at 35° C. and pH 3 for 30 seconds, and then immersed in a 0.1 mass % sodium sulfite aqueous solution for 2 minutes to obtain a composite semipermeable membrane of Comparative Example 2.

[0100] [Comparative Example 3] The membrane obtained in Comparative Example 1 was immersed in a 1% by mass aqueous solution of potassium peroxymonosulfate at 25°C and pH 2 for 30 seconds, and then immersed in a 0.1% by mass aqueous solution of sodium sulfite for 2 minutes to obtain a composite semipermeable membrane of Comparative Example 3.

[0101] [Comparative Example 4] The membrane obtained in Comparative Example 1 was immersed in a 0.4 mass% aqueous sodium nitrite solution at 35° C. and pH 3 for 30 seconds, and then immersed in a 1 mass% aqueous potassium peroxymonosulfate solution at 25° C. and pH 2 for 30 seconds. Next, it was immersed in a 0.1 mass% aqueous sodium sulfite solution for 2 minutes to obtain a composite semipermeable membrane of Comparative Example 4.

[0102] [Comparative Example 5] The membrane obtained in Comparative Example 1 was immersed in a 1 mass% potassium peroxymonosulfate aqueous solution at 25°C and pH 2 for 30 seconds, and then immersed in a 0.4 mass% sodium nitrite aqueous solution at 35°C and pH 3 for 30 seconds. Next, it was immersed in a 0.1 mass% sodium sulfite aqueous solution for 2 minutes to obtain a composite semipermeable membrane of Comparative Example 5. [Comparative Example 6] The membrane obtained in Comparative Example 1 was immersed in a 0.4 mass% aqueous sodium nitrite solution at 35° C. and pH 3 for 30 seconds, and then immersed in a 0.1 mass% aqueous potassium peroxymonosulfate solution at 25° C. and pH 2 for 10 seconds. Next, it was immersed in a 0.1 mass% aqueous sodium sulfite solution for 2 minutes to obtain a composite semipermeable membrane of Comparative Example 6.

[0103] [Table 1]

[0104] [Table 2]

[0105] As shown in Examples 1 to 5, a composite semipermeable membrane in which the separation functional layer contains a crosslinked polyamide having an azo group and a nitro group, and in which the ratio A of the azo group and the ratio B of the nitro group satisfy 0.10≦A / B≦0.50, combines high water production properties with neutral molecule removal performance, and also shows extremely small performance degradation after combined deterioration tests with acids, alkalis, oxidizing agents, etc.

Claims

1. A support membrane and a separation functional layer are provided, The separation functional layer contains a crosslinked polyamide having an azo group and a nitro group, and A composite semipermeable membrane, wherein a ratio A of the azo group and a ratio B of the nitro group in the separating functional layer satisfy 0.10≦A / B≦0.

50.

2. 2. The composite semipermeable membrane according to claim 1, wherein the ratio A of azo groups, the ratio B of nitro groups, and the ratio C of amide groups in the separating functional layer satisfy 0.010≦(A+B) / C≦0.

050.

3. 3. The composite semipermeable membrane according to claim 1, wherein the zeta potential of the surface of the separation functional layer in a pH 7, 10 mM sodium chloride aqueous solution is −70 mV or more and −35 mV or less.

4. 3. The composite semipermeable membrane according to claim 1, wherein the chromaticity b* of the surface of the separating functional layer is 5 or more and 20 or less.

5. A method for producing a composite semipermeable membrane comprising a support membrane and a separation functional layer provided on the support membrane, (a) forming a crosslinked polyamide on the support membrane by polycondensation of a polyfunctional amine and a polyfunctional acid halide; (b) contacting the crosslinked polyamide simultaneously with a compound (I) that reacts with a primary amino group to form a diazonium salt or a derivative thereof, and an oxidizing agent; A method for producing a composite semipermeable membrane comprising the steps of:

6. The method for producing a composite semipermeable membrane according to claim 5, wherein in the step (b), a mass ratio of the oxidizing agent to the compound (I) is 2 or more and 10 or less.

7. 7. The method for producing a composite semipermeable membrane according to claim 5 or 6, wherein the step (b) comprises contacting an aqueous solution containing both the compound (I) and an oxidizing agent with the crosslinked polyamide, the temperature of the aqueous solution being 20° C. or higher and 50° C. or lower, and the contact time with the crosslinked polyamide being 10 seconds or higher and 10 minutes or lower.

8. The method for producing a composite semipermeable membrane according to claim 5 or 6, further comprising a step of contacting the crosslinked polyamide with sodium hydrogen sulfite or sulfite ions after the step (b).

9. The amount of polyfunctional amine contained in the composite semipermeable membrane is 10 mg / m 2 80mg / m or more 2 The method for producing a composite semipermeable membrane according to claim 5 or 6, wherein:

Citation Information

Patent Citations

  • Polyamide membranes with fluoroalcohol functionality

    WO2010096563A1

Cited By

  • Composite semipermeable membrane, composite semipermeable membrane element, water treatment system, and method for manufacturing a composite semipermeable membrane

    JP7917102B1

  • Composite semipermeable membrane, composite semipermeable membrane element, water treatment system, and method for producing composite semipermeable membrane

    WO2026186699A1